Global Dystopias and Colonial Continuities: Reimagining Resistance and Unveiling Neocolonial Structures through Cross-Cultural Analysis of Animated Short Films - Niazi, Shanzae; Musharraf, Sidra; Irum, Sonia (Pakistan Journal of Humanities and Social Sciences, 2025)
This article aims to examine neocolonialism in dystopian animated short films from multiple countries, highlighting its entrenchment within a colonial matrix of hierarchization and systemic destabilization through the continued perpetuation of colonial legacies. The study employs a descriptive, cross-cultural qualitative analysis of ten selected dystopian animated short films, namely Swipe, Shehr e Tabassum, What is Your Brown Number?, Living in a Masked Society, Children, Urbance, Model Citizen, Being Pretty, Avarya, and No Monsters, produced between 2010 and 2022. The findings posit that these films reveal and critique the persistent inequalities and systemic destabilization affecting non-Western states in a postcolonial context. They expose how dystopian fiction, through futuristic imaginaries, critiques forms of domination and oppression still exercised on formerly colonized societies, including totalitarianism, racism, and social subjection. These insights can guide policymakers and cultural institutions in acknowledging and addressing the lingering neocolonial hierarchies embedded in global cultural production, as well as in promoting narratives that resist such hegemonic frameworks.